Aptidão funcional e física de idosos: influência do programa "mexa-se" da academia da saúde - Bortolini, Lucas Sérgio (2024)
Aging naturally involves a functional decline of the human body. However, it is well-known that lifestyle directly affects the speed and intensity of this process. Physical activity is closely related to the quality of life of human beings as it can mitigate the degenerative effects of aging through its impact on both body and mind. This study seeks to evaluate and compare the functional fitness of a group of elderly participants in a weekly physical exercise program called "Mexa-se" at the Health Academy at the Municipal District of Flor do Sertão, Santa Catarina (SC), by analyzing variables and information related to their functional fitness. A sample of 30 elderly individuals was intentionally selected and their participation was voluntary. They were divided into two groups: the Mexa-se group, comprising 15 elderly individuals who regularly attend the Health Academy program and the Control group, comprising 15 elderly individuals who did not attend. The performance of the Mexa-se group was significantly better in the variables flexibility (p=0.050), handgrip strength of the left limb (p=0.031) and cardiorespiratory endurance (p=0.043). The study concludes that regular physical activity has a direct positive influence on the functional fitness of the elderly,enhancing their quality of life, well-being and independence, as they age.